Visual information design of eye-care awareness for children - Liew, Jiun Yui, (Universiti Malaysia Sarawak (UNIMAS), 2014)
The scenario of wearing spectacles among the kids had become a trend in this era. Nonetheless, the awareness of parents about eye-care is still low by virtue of the poor eye health promotion. Through the visual and information data analysis, information design is focused in order to improve the target audience's comprehension about the message to be conveyed through digital media.